Adenosine A1‐receptor blockade impairs the ability of rat pups to autoresuscitate from primary apnea during repeated exposure to hypoxia. Issue 8 (13th August 2015) - Fewell, James E.; Lun, Rongzhi
Abstract Failure of gasping to bring about autoresuscitation from hypoxia‐induced apnea has been suggested to play a role in sudden unexpected infant death. Little is known, however, about factors that influence the ability of gasping to restore life during severe hypoxia in newborns. Given that adenosine modulates cardiac function during hypoxia‐induced apnea and that cardiac dysfunction plays a role in mediating autoresuscitation failure, the present experiments were carried out on 34, 5‐ to 6‐, and 10‐ to 11‐day‐old rat pups to investigate their ability to autoresuscitate from hypoxia‐induced apnea during repeated exposure to hypoxia after adenosine A1‐receptor blockade. Each pup was placed into a temperature‐controlled chamber regulated to 37 ± 1°C and repeatedly exposed to an anoxic gas mixture (97% N2 and 3% CO2) until the occurrence of autoresuscitation failure. One group was studied following administration of the selective adenosine A1‐receptor antagonist 8‐Cyclopentyl‐1, 3, ‐dipropylxanthine (DPCPX) and one group was studied following vehicle. DPCPX significantly attenuated bradycardia during hypoxia‐induced apnea and impaired the ability of both age groups of pups to autoresuscitate during repeated exposure to hypoxia (5–6 days tolerated – vehicle 17 ± 4 vs. DPCPX 10 ± 2 hypoxia exposures [P < 0.05]; 10–11 days tolerated – vehicle 10 ± 2 vs. DPCPX 7 ± 2 hypoxia exposures [P < 0.05]). Death in all pups resulted from the inability of gasping to restore cardiovascular function during hypoxia‐induced apnea although the mechanism of cardiovascular dysfunction/failure was influenced and the occurrence hastened by DPCPX. Thus, our data provide evidence that adenosine acting via adenosine A1‐receptors enhances the ability of rat pups to tolerate repeated exposure to severe hypoxia during early postnatal maturation.